Fuel to the fire: The escalating interplay of attachment and maltreatment in the transgenerational transmission of psychopathology in families living in refugee camps. (October 2021) - Scharpf, Florian; Mkinga, Getrude; Neuner, Frank; Machumu, Maregesi; Hecker, Tobias
Abstract: Maltreatment by parents can be conceptualized as pathogenic escalations of a disturbed parent–child relationship that have devastating consequences for children's development and mental health. Although parental psychopathology has been shown to be a risk factor both for maltreatment and insecure attachment representations, these factors` joint contribution to child psychopathology has not been investigated. In a sample of Burundian refugee families living in refugee camps in Western Tanzania, the associations between attachment representations, maltreatment, and psychopathology were examined by conducting structured interviews with 226 children aged 7 to 15 and both their parents. Structural equation modeling revealed that children's insecure attachment representations and maltreatment by mothers fully mediated the relation between maternal and child psychopathology [ model fit: comparative fit index (CFI) = 0.96; root mean square error of approximation (RMSEA) = 0.05]. A direct association between paternal and child psychopathology was observed ( model fit: CFI = 0.96; RMSEA = 0.05). The findings suggest a vicious cycle, wherein an insecure attachment to a mother suffering from psychopathology may be linked to children's risk to be maltreated, which may reinforce insecure representations and perpetuate the pathogenic relational experience. Interventions targeting the attachment relationship and parental mental health may prevent negative child outcomes.